Aleph (JSTOR)
Aleph explores the interface between Judaism and science and studies the interactions between science and Judaism throughout history. Aleph features full-length articles, brief communications, and notes on recently published books, as well as studies on related subjects that allow a comparative view, such as the place of science in other cultures.
Keywords: Jewish Studies